INTERNATIONAL STANDARDS AND AUTHORIZATIONS OF LABOR INSPECTION IN AGRICULTURE IN CASE OF TERMINATION OF EMPLOYMENT RELATIONSHIP - Radovanović, Vladimir (Economics of Agriculture, 2023)
Agricultural work is the oldest form of work, but the rights of agricultural workers are still not sufficiently protected, especially if their legal position is compared to that of employees in other branches of the economy. One of the tools for improving the legal protection of farmers is through the work of labor inspection, as an important element of control over the application of the relevant legal regulations. Even though the legal status of employees in agriculture has seemingly experienced some normative progress, the situation is unfortunately still far from being ideal, especially regarding the protection of their rights in the employment relationship and the manner in which those rights are exercised in practice. In this regard, this paper will address universal international standards in this area and the compliance of domestic Serbian legislation with the relevant conventions and recommendations of the International Labor Organization. Additionally, a particular focus will be placed on protecting agricultural workers against illegal dismissal.